2010
DOI: 10.1167/iovs.10-5212
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Changes in the Rat Optic Nerve Following Short-term Intermittent Elevations in Intraocular Pressure

Abstract: Controlled daily 1-hour IOP elevations can be performed with an adjustable vascular loop in rats. After only 6 weeks, intermittent elevations in IOP produce changes in optic nerve consistent with early degeneration reported in chronic models of glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 53 publications
4
52
0
Order By: Relevance
“…There was, however, a marked disparity between the potent RGC neuroprotective effect of siRTP801 and the relatively limited axon regeneration, confirming that axon regeneration is not inevitable in surviving RGCs. 19,71 A typical rodent ON contains approximately 100,000 RGC axons, 72 and thus the number of regenerating axons we observed represents a regenerative response in fewer than 0.1% RGCs. Nonetheless, our results complement the increasing literature implicating the PI3K/ Akt/mTOR pathway as a mediator of axon regeneration in several models of CNS injury.…”
Section: Discussionmentioning
confidence: 96%
“…There was, however, a marked disparity between the potent RGC neuroprotective effect of siRTP801 and the relatively limited axon regeneration, confirming that axon regeneration is not inevitable in surviving RGCs. 19,71 A typical rodent ON contains approximately 100,000 RGC axons, 72 and thus the number of regenerating axons we observed represents a regenerative response in fewer than 0.1% RGCs. Nonetheless, our results complement the increasing literature implicating the PI3K/ Akt/mTOR pathway as a mediator of axon regeneration in several models of CNS injury.…”
Section: Discussionmentioning
confidence: 96%
“…Different studies have used different parameters to assess GC-related retinal morphometric changes such as number of RGC in the unit area (Koeberle and Ball, 1998;Lam et al, 1999), number of RGC in the field of view (Joos et al, 2010), volume of RGC (Zhang et al, 2000), linear density of RGCs (Chávez et al, 2003;Sun et al, 2011;Takahata et al, 2003) thickness of the GCL and IR (Chávez et al, 2003;Sun et al, 2011;Takahata et al, 2003;Lam et al, 1999). Our investigation revealed that linear density is the most sensitive parameter to evaluate cell loss in the GCL.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 This minimally invasive technique employed the concept of oculopression to produce elevated IOP. [10][11][12] An advantage of the suture compression model is that it is not associated with ocular tissue penetration or traumatization, and therefore relatively preserves the immune privilege of the eye. It was reported that a mild, chronic IOP elevation was induced for at least 15 weeks following an initial IOP spike that appeared immediately after suture placement.…”
mentioning
confidence: 99%